Ctrip: China's Online Travel Platform – Local Giant or Global Competitor? - Tianyi Shao; Martin Kenney (The Research Institute of the Finnish Economy (ETLA), 2018)
In a large number of sectors, Chinese internet platform firms have grown to enormous size leveraging a rapidly growing, largely protected domestic market This paper describes the formation and growth of the largest Chinese travel and tourism platform, Ctrip within the context to the changing Chinese economy. In 2018, Ctrip was one of the largest travel platforms in the world and, though still significantly smaller than the US travel and tourism platforms that dominate most of the rest to the world, it was growing far faster than them. Ctrip's remarkable success is explained within the context to the rising tide of Chinese tourism. The paper explores Ctrip's recent globalization strategies suggesting that it intends to expand beyond just serving the Chinese market or Chinese tourists in global markets. At this point, the globalization strategy appears to have two prongs: The first prong has been using its enormous cash flow to acquire or co-invest in local firms that dominate other developing country markets that are expanding rapidly. The two cases in point are its equity investment in the Indian travel giant, MakeMyTrip, and investments in Southeast Asia. The second prong is investing or acquiring firms/websites in developed nation markets that can either service the enormous flow of Chinese tourists it controls or provide services to Western travelers. For these investments, Ctrip can provide infrastructural and capital support to allow these operations to expand more quickly. It is uncertain how successful Ctrip's initiatives in international markets will be. However, given that Chinese tourism is likely to continue its rapid growth and that Ctrip monopolizes this market, it has significant financial resources, enormous leverage in directing this flow of tourists for strategic advantage, and a rapidly developing capability in analyzing the enormous inflow of data that it receives. For the reasons we describe, Ctrip is likely to be an increasingly formidable competitor to the US global travel and tourism platform giants, Expedia, Priceline, and TripAdvisor.
Keywords: 330